REFLECTIONS ON THE USE OF CONJOINT ANALYSIS AS A DUAL METHODS IN NEUROMARKETING RESEARCH - Nik Nur Azhani Anuar; Salmi Mohd Isa (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Neuromarketing techniques provide valuable insights regarding consumer’s subconscious decision-making experience. However, there are traditional methods well-favoured for its ability to explain consumer’s conscious trade-offs known as conjoint analysis. Although the two methods differ greatly, both possess qualities that benefits and limits researchers the entire duration of a study. Therefore, comparison of the methods could provide opportunities for improvement. Recently, integration of neuromarketing techniques and conjoint analysis are utilized under one study simultaneously and resulted in a more holistic understanding of a controlled situation. Further analysis on neuromarketing techniques, conjoint analysis, and dual method may enlighten researchers on an effective and efficient alternative of data collection to obtain higher quality of information. This mini review articulate characteristics of both methods and identifies significance of a dual method in research efforts.